Utilization of Crude Intracellular Chitinase Enzyme from Providencia stuartii for Glucosamine Production from Shrimp Shells - Hardoko Hardoko; Titri Siratantri Mastuti; Desy Puspasari; Yuniwaty Halim (Dept. of Chemical Engineering, Diponegoro University, 2019)
Chitin hydrolysis using enzyme is one of the methods to produce glucosamine in shorter time compared to using microbial cells, but the ability to produce glucosamine at enzyme’s optimum condition is influenced by substrate concentration and fermentation time. The objective of this research was to determine the optimum substrate concentration and fermentation time of shrimp shells’ chitin to produce glucosamine at the optimum pH and temperature of crude intracellular chitinase enzyme from Providencia stuartii. Method used was experimental method, started by extraction of intracellular enzyme from P. stuartii, followed by determination of optimum pH and temperature of enzyme. The optimum condition was used for experiment of shrimp shells’ chitin fermentation with treatments of chitin substrate concentration (0.5; 1.0; 1.5; 2.0%) and fermentation time (2, 4, 6 and 24 hours). Results showed that optimum enzyme activity occurred at pH of 5.0 and temperature of 40oC, which was about 6.03 U/ml. Concentration of chitin substrate and fermentation time influenced the amount of glucosamine obtained. Fermentation of shrimp shells’ chitin using crude intracellular enzyme was optimum at 1.0% substrate concentration and 6 hours fermentation time, which produced glucosamine about 1680.06±58.49 ppm. Keywords: intracellular chitinase enzyme, glucosamine, shrimp shells’ chitin, P. stuartii